Single-molecule studies on the label number distribution of fluorescent markers - Grußmayer, Kristin Stefanie; Kurz, Anton; Herten, Dirk-Peter (ChemPhysChem, 2014)
Over the past decade, a vast variety of different fluorescent labeling systems have emerged for use in fluorescence microscopy and fluorescence-based analytical techniques. A difficulty frequently arising when quantifying fluorescently labeled samples is that the number of labels per protein is neither well defined, for example, due to multiple functional groups that can undergo covalent coupling with activated dyes, nor well known, for example, due to limited methods mostly estimating ensemble averages. Herein, we use a recently established method that evaluates the statistics of multiple photon detection events to measure the label number distribution of different fluorescent marker molecules at the single-molecule level. We tested five different far-red dyes frequently used for fluorescence labeling and found all of them suitable for our counting method. We used two dyes, ATTO647N and Alexa647, to investigate the label number distribution of fluorescently labeled proteins. In the experiments, we found that the label number distribution of antibodies and streptavidin has a significant fraction of molecules labeled with two, three, or more fluorophores. In contrast, the distribution of label numbers for nanobodies resembles the one acquired for SNAP-tag, which can have a maximum of one label per protein. This is also reflected in the ensemble degree of labeling, which is in good agreement for the latter samples, whereas stronger deviations were observed for antibodies and streptavidin. Our single-molecule studies enable full characterization of the label number distribution for various fluorescent markers. This work puts quantitative studies on the stoichiometry of fluorescently tagged oligomers and protein aggregates into perspective.